Convenient tumor 3D spheroid arrays manufacturing via acoustic excited bubbles for in situ drug screening. Issue 6 (8th February 2023) - Zheng, Jingjing; Hu, Xuejia; Gao, Xiaoqi; Liu, Yantong; Zhao, Shukun; Chen, Longfei; He, Guoqing; Zhang, Jingwei; Wei, Lei; Yang, Yi
Abstract : Rapid construction of size-controllable 3D tumor spheroid arrays based on acoustic bubbles in microfluidic chips for in situ drug response testing. Abstract : The quick and convenient fabrication of in vitro tumor spheroids models has been pursued for clinical drug discovery and personalized therapy. Here, uniform three-dimensional (3D) tumor spheroids are quickly constructed by acoustically excited bubble arrays in a microfluidic chip and performed drug response testing in situ . In detail, bubble oscillation excited by acoustic waves induces second radiation force, resulting in the cells rotating and aggregating into tumor spheroids, which obtain controllable sizes ranging from 30 to 300 μm. These spherical tumor models are located in microfluidic networks, where drug solutions with gradient concentrations are generated from 0 to 18 mg mL −1, so that the cell spheroids response to drugs can be monitored conveniently and efficiently. This one-step tumor spheroids manufacturing method significantly reduces the model construction time to less than 15 s and increases efficiency by eliminating additional transfer processes. These significant advantages of convenience and high-throughput manufacturing make the tumor models promising for use in tumor treatment and point-of-care diagnosis.